Dizzy Patients: Diagnosis and Treatment - McGee, Steven R. (1995)
This discussion was selected from the weekly Grand Rounds in the Department of Medicine, University of Washington School of Medicine, Seattle. Taken from a transcription, it has been edited by Jonathan Drachman, MD, Chief Medical Resident; Henry Rosen, MD, Professor and Associate Chair; and Paul Ramsey, MD, Professor and Chair of the Department of Medicine.